Home-based exercise training improves capillary glucose profile in women with gestational diabetes - Halse, Rhiannon; Wallman, K.; Newnham, J.; Guelfi, K. (Lippincott Williams & Wilkins, 2014)
PURPOSE: Regular maternal exercise may play an important role in the management of gestational diabetes mellitus (GDM), yet specific exercise guidelines to achieve glycemic control have not been established. Furthermore, many women remain sedentary during pregnancy because of perceived barriers to exercise participation. This study examined the effectiveness of a home-based cycling program commenced upon diagnosis of GDM on daily fasting and postprandial blood glucose levels, glycosylated hemoglobin (HbA1c), and the response of glucose and insulin to a 75-g oral glucose load. METHODS: Forty sedentary women (28.8 ± 0.9 wk of gestation) were randomized to either home-based exercise training in combination with conventional management (EX, n = 20) or to conventional management alone (CON, n = 20) until week 34 of pregnancy. RESULTS: Mean compliance to the supervised exercise training was 96%, and no adverse effects were reported. Capillary glucose concentration was acutely reduced in response to each cycling session (6.3 ± 0.8 mM to 4.9 ± 0.7 mM, P < 0.001). Overall, the EX group had lower mean daily postprandial glucose concentrations throughout the intervention compared with that in the CON group (P < 0.05) despite consuming a greater proportion of dietary carbohydrate (P < 0.05). No differences were observed between groups with respect to HbA1c or the glucose and insulin response to oral glucose ingestion postintervention (P > 0.05). CONCLUSIONS: A home-based cycling program may help to maintain daily postprandial normoglycemia in women with diet-controlled GDM. © 2014 by the American College of Sports Medicine.